Angioneurotic orolingual oedema following thrombolysis in acute ischaemic stroke - Wallon, D (BMJ Publishing Group, 2010)
Alteplase used for thrombolysis in ischaemic stroke may be complicated by orolingual acute angioedema (OAA), a rare but potentially life-threatening side effect. We report the case of a 32-year-old woman who over 24 h experienced OAA after thrombolysis for an acute ischaemic left hemispheric stroke. We discuss the pathophysiology of this rare phenomenon.